Entomofauna associada à fase de implantação de sistemas agroflorestais utilizando modelo Nelder - Costa, Ângela Cecília Freire (2013)
Insects are one of the important elements for the Agroforestry action and handling, once they can act as material decomposers, cultivations powerful pollinator and herbivorous. This work aimed to evaluate the Entomological Fauna which is associated to implementation period of Agroforestry Systems, using Nelder s pattern. The research was realized on Experimental Fields of Agroecological Studies belonging to Instituto Federal de Educação, Ciência e Tecnologia de Sergipe, at Tabuleiros Costeiros region, in São Cristóvão SE city. The insects related to eight Agroforestry Systems: eucalyptus + corn (SEM), eucalyptus + beans (SEF), teak + beans (STF), teak + corn (STM), gliricidia + beans (SGF), gliricidia + corn (SGM), leucaena + corn (SLM ) and leucaena + beans (SLF). The monthly collects of insects were realized from February to September/2012, with pitfalls traps aids. In all evaluated systems, the insects that are from Hymenoptera line contrasted in the previous period to the implementation of Agroforestry Systems, while the partners of Diptera line were more expressive in the post period. Coleoptera was the order of the richest families in both periods. The family Formicidae was the most representative, independently of the collect period. The biggest number of insects was noted after the implementation of Agroforestry Systems. The SLF presented the hugest number of individuals, the SLM and SLF the hugest wealthy of families and the SEF, the hugest variety of insect families. The composition of insect families was highly similar among the evaluated Agroforestry Systems. The obtained results indicate that the rainy period, the available food offer, the variety of vegetal species, the distance among the systems and the collect method which were used, influenced in the Entomofauna levy associated to Agroforestry Systems.